Pemberdayaan KWT Laras Pandowo Melalui Pelatihan Pengolahan Pangan Lokal Di Desa Pandowoharjo Sleman: Empowerment of Laras Pandowo Women's Farmer Group through Local Food Processing Training in Pandowoharjo Village, Sleman - Rida Kalina; Muhammad Fanni; Elisa Angraini Wulan Sari; Anisa Salsabila; Erinta Silvianti Oktaviana; Fahrani Listadya Supriyanto; Fitria Hasna Zhafirah; Izhna Komala Maharani; Muhammad Fajar Sya’bani; Rahmadi Dwi Setiawan; Raja Zhafif Raditya Harahap; Rasyad Alif; Savana Zahra Maharani; Siti Nurhayati; Syahrul Aidil Putra; Arsyad Cahya Subrata (UKInstitute, 2026)
Abstract. The 2025 Student Organization Capacity Building Program (PPKO) of the Ahmad Dahlan University Student Association (HMTP) is a concrete manifestation of the implementation of the Tri Dharma of Higher Education, particularly in the area of community service. The program partner is the Laras Pandowo Women's Farmers Group (KWT) in Pandowoharjo Village, Sleman, which boasts abundant local food potential but has not been optimally utilized. The goal of this program is to improve the entrepreneurial skills and insight of KWT members through training in processing local food ingredients into catfish basreng (basreng), catfish floss (flour), and chili flakes as a form of local food diversification. The implementation method includes preparation, Participatory Rural Appraisal (PRA), training, mentoring, evaluation, and follow-up. The results of the activity showed an increase in participants' knowledge and skills of 56.9%, namely calculated from 58 points before the training to 91 points after the training. In addition, there was an average increase in side income of 55.7%, from Rp 227,272 before training to Rp 353,846 after training, which indicates the real application of training results in household economic activities. Participants were able to develop innovative flavors, packaging designs, and simple marketing strategies through social media. This program has successfully fostered the entrepreneurial spirit of village women and is the first step towards economic independence based on local potential. Abstrak. Kegiatan Program Penguatan Kapasitas Organisasi Kemahasiswaan (PPKO) HMTP Universitas Ahmad Dahlan tahun 2025 merupakan wujud nyata pelaksanaan Tri Dharma Perguruan Tinggi, khususnya dalam bidang pengabdian kepada masyarakat. Mitra kegiatan adalah Kelompok Wanita Tani (KWT) Laras Pandowo di Desa Pandowoharjo, Sleman, yang memiliki potensi bahan pangan lokal melimpah namun belum termanfaatkan secara optimal. Tujuan kegiatan ini adalah meningkatkan keterampilan dan wawasan kewirausahaan anggota KWT melalui pelatihan pengolahan bahan pangan lokal menjadi basreng lele, abon lele, dan chili flakes sebagai bentuk diversifikasi pangan lokal. Metode pelaksanaan meliputi tahapan persiapan, Participatory Rural Appraisal (PRA), pelatihan, pendampingan, evaluasi, dan tindak lanjut. Hasil kegiatan menunjukkan adanya peningkatan pengetahuan dan keterampilan peserta sebesar 56,9%, yaitu dihitung dari 58 poin sebelum pelatihan menjadi 91 poin setelah pelatihan. Selain itu, terdapat peningkatan pendapatan sampingan rata-rata sebesar 55,7%, dari Rp 227.272 sebelum pelatihan menjadi Rp 353.846 setelah pelatihan, yang menandakan penerapan nyata hasil pelatihan dalam aktivitas ekonomi rumah tangga. Peserta mampu mengembangkan inovasi rasa, desain kemasan, dan strategi pemasaran sederhana melalui media sosial. Program ini berhasil menumbuhkan semangat kewirausahaan perempuan desa dan menjadi langkah awal menuju kemandirian ekonomi berbasis potensi lokal.